2019
DOI: 10.3329/bjms.v18i2.40689
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Acute and Chronic Forms of Leukemia in Various Regions of Khyber Pakhtunkhwa, Pakistan: Needs Much More to be done!

Abstract: Background and objective: Leukemia is one of the fatal diseases and their morbidity and mortality rates increases day by day all over the world. This piece of research study was designed in order to find out the prevalence of different types of leukemia in Khyber Pakhtunkhwa, Pakistan during January 2015 to December 2016. Material and Method: The retrospective research study was carried out at Institute of Radiotherapy and Nuclear Medicine (IRNUM) Peshawar. A data of 400 admitted patients of leukemia wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 8 publications
0
13
0
1
Order By: Relevance
“…A similar study reported leukemias among 24.76% of the studied bone marrow examined cases, with acute lymphoblastic leukemia as the commonest hematological malignancy 23 . In contrast, a more recent study from KPK reports a high prevalence of acute leukemia than chronic leukemia 24 . Most frequent among acute leukemias were acute lymphocytic leukemia (49.5%) followed by acute myelogenous leukemia (31.25%), while among chronic conditions, chronic myelogenous leukemia was observed in only 10% of the enrolled population, followed by chronic lymphocytic leukemia (9.25%).…”
Section: Discussionmentioning
confidence: 75%
“…A similar study reported leukemias among 24.76% of the studied bone marrow examined cases, with acute lymphoblastic leukemia as the commonest hematological malignancy 23 . In contrast, a more recent study from KPK reports a high prevalence of acute leukemia than chronic leukemia 24 . Most frequent among acute leukemias were acute lymphocytic leukemia (49.5%) followed by acute myelogenous leukemia (31.25%), while among chronic conditions, chronic myelogenous leukemia was observed in only 10% of the enrolled population, followed by chronic lymphocytic leukemia (9.25%).…”
Section: Discussionmentioning
confidence: 75%
“…Além disso destaca-se a importância de um estilo de vida saudável materno por meio de alimentação saudável, atividade física regular, sem No Brasil tanto as crianças como os adolescentes do sexo masculino foram mais afetados pela leucemia que o sexo feminino (Figura 3). Em uma província do Paquistão, a leucemia linfoide aguda foi mais prevalente em crianças e adolescentes do sexo masculino (AHMAD et al, 2019). Mas na Suécia, estudo evidenciou que a leucemia é similar entre os sexos sendo 13,2 por 100.000 casos em homens e 13,9 por 100.000 casos em mulheres (JULIUSSON et al, 2016).…”
Section: Resultsunclassified
“…This was in concurrent findings reported in Bangladesh in which HM was dominant in male patients with a male to female ratio of 2.2:1, and leukemia was more prevalent in male patients and male to female ratio was 1.8:1, in India male preponderance with a male to female ratio of 2.3:1, in Pakistan HM is more common in male with the ratio of 2.5:1. 9,30,40,43 The possible justification might be that male individuals are comparatively more exposed to the occupational and environmental carcinogenic agents which are at higher risk to the incidence of all kinds of leukemia. 44 In the current study, the myeloid type of HM was dominant and accounted for 53.8% of cases and CML accounted for 30.8% of the cases whereas AML accounted for 23% out of the confirmed cases.…”
Section: Discussionmentioning
confidence: 99%